EASYCHATBOT (CIPEEX, 2024)
"We are EasyChatBot, a startup that is revolutionizing the way companies communicate withtheir customers. Our platform allows users to create and customize their own chatbots easilyand intuitively. Our user-friendly application enables users to create their own customchatbots in minutes, without the need for programming knowledge. They can choose from avariety of templates and personalize them with their unique brand, voice, and tone.Furthermore, our platform offers integrations with leading marketing automation and CRMtools in the market, allowing users to automate the entire customer journey."
Keywords: Chat; Personalize; Programming